2014
DOI: 10.3233/bmr-140468
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between massage and routine physical therapy in women with sub acute and chronic nonspecific low back pain

Abstract: It can be concluded that both massage therapy and routine physical therapy are useful for sub acute and chronic nonspecific low back pain treatment especially if accompanied with exercise. However, massage is more effective than other electrotherapy modalities, and it can be used alone or with electrotherapy for the treatment of patients with low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
2
19
1
2
Order By: Relevance
“…In line with the current study, the results of trials (20,21) indicate that massage is effective in reducing pain and functional disability, as well as improving mobility and psychological well-being, in chronic low back pain, especially if accompanied with exercises (20).…”
Section: Discussionsupporting
confidence: 87%
“…In line with the current study, the results of trials (20,21) indicate that massage is effective in reducing pain and functional disability, as well as improving mobility and psychological well-being, in chronic low back pain, especially if accompanied with exercises (20).…”
Section: Discussionsupporting
confidence: 87%
“…The frequent study of back pain massage probably relates to the high incidence of low back pain as compared to other forms of pain, although carpal tunnel pain and smart thumb syndrome pain are becoming increasingly common. In one study, women with chronic low back pain were randomly assigned to massage therapy or physical therapy groups [41]. Stretching exercises were added to both the massage therapy and the physical therapy.…”
Section: Pain Syndromes (See Table 3)mentioning
confidence: 99%
“…Th ere is a strong evidence about the eff ectiveness of therapeutic exercises for patients with LBP, some authors reported that therapeutic exercises are very eff ective for back fl exibility, pain management and improvement of ability in daily life activities (Hayden, Tulder, & Tomlinson, 2005) (Garcia et al, 2013;Dunsford, Kumar, & Clarke, 2011;Kamali, Panahi, Ebrahimi, & Abbasi, 2014. According our survey we can conclude that is strong evidence about the eff ectiveness of deep tissue massage for patients with low back pain regarding the pain and mobility, although the evidence showed that is very little confi dence that massage is an eff ective treatment for chronic LBP (Farber & Wieland, 2016). But when massage is combined with therapeutic exercises and modalities showed to be very eff ective treatment for patients with chronic LBP (Bervoets, Lujisterburg, Alessie, & Bujis, 2015;Cherkin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%